Effects of the state trade countries upon the commodity markets - Dietrich Kebschull (Intereconomics, 1978)
This article proves that a good deal is to be said for an abandonment by the state trade countries of their financial abstention and for their active financial participation in the Integrated Programme for Commodities. At UNCTAD IV in Nairobi the Third World nations first presented their requests to the state trade countries, in an unmistakable manner, for more extensive development-policy contributions.
Keywords: 330; Raw Materials